Legal analysis of the implementation of insurance programs in the Republic of Kazakhstan to prevent accidents at work and assess the need for investments in safe work at the expense of the insurance fund formed in the compulsory accident insurance system - Smatlayev, B.M.; Abikenova, Sh.K.; Saktaganova, I.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Accident insurance systems that adhere to international standards and approaches form an essential element of occupational safety management systems, serving to enhance working conditions while mitigating occupational risks while safeguarding our country's workforce. Insurance is one of the most cost-effective regulatory mechanisms available today for improving working conditions while safeguarding workers. As part of the Order of the Prime Minister's of the Republic of Kazakhstan dated December 29, 2020 to develop and implement the National Labor Protection Program outlined there, which mandated developing an effective National Labor Protection System by uniting government with social partners, on January 20, 2022 the Concept for Labor Safety until 2030 was approved. As part of the implementation of the Action Plan to Increase Occupational Safety in Kazakhstan until 2025 approved by Decree of the Government of the Republic of Kazakhstan on June 17, 2021, No 419, several measures designed to strengthen occupational safety management systems within enterprises have been introduced.